Antibiotic resistance pattern of fish bacteria from freshwater and marine sources in Andamans - Shome, Rajeshwari; Shome, B R (Indian Journal of Fisheries, 2011)
Out of 326 total bacterial isolates from infected freshwater and marine fishes having no history of either prophylactic or therapeutic use of antibiotics, 145 were identified atleast upto genus level. The predominanting genera were Aeromonas, Pseudomonas, Vibrio, Acinet,obacter, Enterobacter, Alcaligenes, Plesiomonas, Edwardsiella, Staphylococcus and Nocardia. In this study 88 of the identified bacteria belonging to 10 genera were tested for resistance pattern against 26 different antibiotics by disc diffusion method in Muller-Hintor agar. The resistance level against streptomycin, penicillin and ampicillin was exhibited by more than 60 per cent of the bacteria and oxytetracycline was most effective in commonly used tetracycline group of antibiotics. None of the isolates was sensitive to all the 26 antibiotics, whereas resistance in any single isolate was found to be against a maximum of 14 antibiotics. Abundance of natural single and multiple antibiotic resistance was demonstrated to be upto the upper limit of 3.7 and 97.1 % respectively. The situation appears to be alarming as this antibiotic resistance gene pool could be a potential threat to humans and therefore is of public health significance.